THE EFFECT OF VARIOUS LOCATION AND SOLVENT TO SAMBILOTO (Andrographis paniculata (Burm.f.) Nees) PHYTOCHEMICAL PROFILES - I Putu Priyasana; Agung Endro Nugroho; Soni Siswanto; Dyaningtyas Dewi Pamungkas Putri; Yosi Bayu Murti (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2023)
Background: Sambiloto (Andrographis paniculata (Burm.f.) Nees) is one of the traditional medicines that contain multiple phytochemical compounds. Every location has its characteristic that affects the metabolic process of phytochemical compounds. Apart from that, the extraction solvent also plays an essential role in attracting compounds in sambiloto. The solvent is related to the polarity and can affect the phytochemical profile. Objective: This research aims to determine the effect of the various location and extraction solvent of sambiloto on its phytochemical profile. Methods: Sambiloto from Denpasar (Dps), Sukoharjo (Skj), and Sleman (Slm) was extracted (1:10 w/v) using ultrasonic-assisted extraction in methanol 100% (MeOH100) and methanol 50% (MeOH50). In water solvents, extraction is carried out using the infusion method. Fingerprint analysis using HPTLC-Densitometry. The data obtained was analyzed further using principal component analysis (PCA). Results: Fingerprint analysis obtained peak data that varied in each extraction solvent. There are four major peaks in the chromatogram profile of each solvent. The peak chromatogram for each solvent also shows differences at each location. PCA analysis shows that the phytochemical content of sambiloto extract is divided into three main clusters. The distribution of the clusters is based on variations in the extraction solvent. Variations in location for each sambiloto also influence its phytochemical profile. However, these variations are still in the same quadrant for each solvent. Conclusion: The solvent determines more variations in the phytochemical profile of sambiloto extract than the various location. Keywords: Sambiloto; Solvent; Location; Phytochemical; Principal Component Analysis